Global Financial Crisis and Stock Return Volatility in India - Mishra, P. K.; Das, K. B.; Pradhan, B. B. (Indian Journal of Finance, 2010)
In recent years, there has been a lot of noise in the media about stock market volatility. Market volatility has drastically increased in recent days and emerging as well as mature economies have been passing through a turbulent period, as reflected in all financial markets and asset classes. In the last year, we had been bombarded by media coverage of the financial crisis in US (the credit crisis, bankruptcies of US financial institutions, the bailout plan, etc.) which had added to this volatility. Market volatility had spiked, and political nations experienced turbulence that spilled over to all capital markets. The global economic slowdown, the US real estate decline, the credit crisis and the reversal in the resources trend created a great deal of turbulence and worry in the capital markets. Financial institutions and other companies around the world have been affected by volatility in the share and property markets.Shares and properties have been the asset types most affected by the recent market volatility. They are known as growth assets, and whilst they are inclined to a higher amount of risk compared to defensive asset types such as cash or fixed interest, they are also known for delivering higher returns over the long term. The relationship between risk and return cannot be avoided. The higher the risk, the higher the potential return.